Assessing the water quality in coastal aquifer of Chennai, India - a case study. (2017) - Annapoorani, A.; Murugesan, A.; Ramu, A.; Renganathan, N.G.
To assess the groundwater quality and seawater intrusion in Chennai, the study has been carried out in June 2011. All the physico-chemical parameters were measured. Hard rock and sedimentary rock formation has been determined using the sodium/chloride ratio. Cross plots of bicarbonate%chloride versus TDS indicate that water samples in S1 zone were saline in nature. According to the hydrochemical analysis, except water samples in S2 zone, other groundwater samples are suitable for domestic purpose. Langelier saturation index has been used to identify the nature of water, especially the acidity or basicity of water. Seawater mixing index has been calculated using the concentrations of sodium, magnesium, chloride and sulphate. From this study, we concluded that high levels of sodium in S1 and S5 indicate that seawater intrusion takes place in this zone. Based on Gibbs calculation, rock water interaction was dominant in S3 and S4 zones, and evaporation is dominant in S1, S2 and S5 zones. Seawater mixing index was found to be a maximum of 8.72% in S1 and S2 zones.